Nanodots decorated asymmetric metal–insulator–metal waveguide resonator structure based on Fano resonances for refractive index sensing application. (5th June 2020) - Butt, M A; Kazanskiy, N L; Khonina, S N
Abstract: The optical sensors are widely used in biological, chemical and food processing industries for refractive index measurement. A novel metal–insulator–metal square ring resonator configuration is introduced where a nano-slit is diagonally positioned on two opposite sides of the square ring and cavity is decorated with a set of silver nanodots. The resonator's spectral properties are thoroughly studied by varying the geometric parameters using the finite element method. The sensitivity of the proposed design is improved by regularly positioning the array of nanodots in the cavity where the concentration of E-field is high, as a result, the surface plasmon polaritons (SPPs) are intensified at the boundaries of the dots which enhances the interaction between SPPs and the ambient medium. The device sensitivity can be improved by increasing the size of the nanodots. The maximum sensitivity offered by standard square ring resonator is 1520 nm RIU −1 while the maximum sensitivity of up to 2464 nm RIU −1 can be achieved by adding 16 nanodots of 10 nm radius in two long sides of the cavity in the standard ring resonator. We believe that our findings are useful for the compact and highly sensitive sensor designs and may further enhance the integration level of the integrated optical circuits.